2014
DOI: 10.3109/09540261.2014.914473
|View full text |Cite
|
Sign up to set email alerts
|

‘Following the word of God’: Empirical insights into managerial perceptions on spirituality, culture and health

Abstract: This article focuses on managers in a selected South African organization and the connections they draw between mental health, culture and spirituality within the workplace. The aim is to gain a deeper understanding of the interrelationships in this complex and growing scientific discourse and to respond to the research question of how mental health, culture and spirituality are interrelated from a managerial perspective. The study follows an inductive single case study approach within the phenomenological par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
5

Relationship

3
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Phipps (2012), for example, uses the term "catalytic engagement with faith" to mean personal experiences that transform one's outlook (181) and a "foundational level of engagement where a personal experience is placed in a context larger than self." Spirituality is associated with experiences of inner peace, and according to Chatters (2000) and other health scholars it involves a positive worldview (see e.g., Mayer & Viviers, 2014). As mentioned previously, religiosity and spirituality are deeply ingrained in the African context (Paris, 1995), and this appears to be especially true for women (Ngunjiri, 2010).…”
Section: The Role Of Spiritualitymentioning
confidence: 91%
“…Phipps (2012), for example, uses the term "catalytic engagement with faith" to mean personal experiences that transform one's outlook (181) and a "foundational level of engagement where a personal experience is placed in a context larger than self." Spirituality is associated with experiences of inner peace, and according to Chatters (2000) and other health scholars it involves a positive worldview (see e.g., Mayer & Viviers, 2014). As mentioned previously, religiosity and spirituality are deeply ingrained in the African context (Paris, 1995), and this appears to be especially true for women (Ngunjiri, 2010).…”
Section: The Role Of Spiritualitymentioning
confidence: 91%
“…Findings across studies indicated that the main theme on individual level centred around a perceived need to find purpose, meaning, and significance in work (De Klerk et al, 2006;Fatoki, 2019;Honiball et al, 2014;Kotze et The perceived importance of spirituality in the workplace was clear on an individual level. However, studies indicated that practices that build spiritual capacity remained something that mostly happened outside the work context, even though it leads to perceived positive Original Research www.koersjournal.org.za behaviours and constructive impact benefits in the workplace itself (De Klerk et al, 2006;Honiball et al, 2014;Mayer & Viviers, 2014;Mohan & Uys, 2006).…”
Section: Personal Level Manifestations and Effectsmentioning
confidence: 99%
“…EHEs are often studied in the context of mental health, meaningfulness, spirituality, and transformative change throughout life (Mayer & Viviers, 2014a, 2014b). They might lead to a change in basic attitudes and behavior (von Lucadou & Wald, 2014), or, if experienced negatively, to spiritual crisis (Wardell & Engebretson, 2006).…”
Section: Exceptional Human Experiencesmentioning
confidence: 99%